Group Theoretical Treatment of Substituted Saturated Fullerenes (C20H20-nXn) - Gupta, D. K.; Singh, S.; Sharma, L. N.; Agrawal, V. P. (Journal of Nepal Chemical Society, 2009)
An Investigation of the effects of various homosubstitutions on the symmetry group of saturated fullerene (C20H20-nXn) has been done. In substituted saturated fullerene (C20H20), tri and tetra substitutions in carbons within one hemisphere reduces the point group to Cs, whereas mono, di & penta substitutions at adjacent vertices within one hemisphere give C3v, C2v, and C5v, respectively. It has been found that di substitution in both hemispheres give the highest degree of symmetry. DOI: 10.3126/jncs.v23i0.2095 J. Nepal Chem. Soc., Vol. 23, 2008/2009 Page:43-44